1998
DOI: 10.1007/bf02787348
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of cranial metastases of extrapulmonary small cell carcinoma with chemotherapy alone

Abstract: Extrapulmonary small cell carcinoma (EPSCC) is a distinct clinical and pathological entity other than small cell carcinoma of the lung. We present a case with EPSCC, with neurologic impairment due to brain metastases at initial diagnosis, which showed a complete response to combination chemotherapy. A 55-year-old male patient was first admitted with a mass of 6 x 6 cm in diameter in the right cervical region. The diagnosis of small cell carcinoma was entertained with immunohistopathologic and light microscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The route by which tumor cells migrate to the less common sites in the cervical spine is not known. Orhan et al [8] suggested that the anastomoses between the drainage of the pelvic veins and systemic veins play important roles in the metastasis of the lower cervical spine. The symptoms and signs at the time of diagnosis of metastatic spinal cord compression in patients with colorectal cancer include back pain (97%), weakness (69%), sensory complaints (23%), radiculopathy (54%), spine tenderness (63%) and bowel or bladder incontinence (54%) [9].…”
Section: Discussionmentioning
confidence: 99%
“…The route by which tumor cells migrate to the less common sites in the cervical spine is not known. Orhan et al [8] suggested that the anastomoses between the drainage of the pelvic veins and systemic veins play important roles in the metastasis of the lower cervical spine. The symptoms and signs at the time of diagnosis of metastatic spinal cord compression in patients with colorectal cancer include back pain (97%), weakness (69%), sensory complaints (23%), radiculopathy (54%), spine tenderness (63%) and bowel or bladder incontinence (54%) [9].…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies (n = 14) were included in the current analysis ( Figure 6) [16][17][18][19][20][21][22][23] . Studies that did not provide separate information for patients with LNEPSCC [29][30][31][32][33][34][35][36][37][38][39][40][41] , and the treatment given or follow up were not included in the current review [42][43][44][45][46][47][48][49][50] .…”
Section: Systematic Reviewmentioning
confidence: 99%
“…First described in 1930 [2] , much needs to be determined about natural history and clinical behaviour of EPSCC. EPSCC is known to involve gastrointestinal tract (esophagus, stomach, liver, bile ducts, intestines and pancreas) [3][4][5] , genitourinary tract (kidney, ureter, pelvis, bladder) [6][7][8][9][10] , head and neck region (tonsils, larynx, nasopharynx, and paranasal sinuses) [11][12][13][14] , bones [15] and lymph nodes (locoregional or distant) [16][17][18][19][20][21][22][23] . Although, EPSCC has histological similarity with small cell lung cancer, it has a different biological behaviour [1,24,25] .…”
Section: Introductionmentioning
confidence: 99%
“…Management usually requires immediate treatment of the brain tumor followed by periodic reevaluation for a primary tumor. Several reports have described the clinical outcome in these patients,1, 2, 5–10 but the authors derived differing conclusions from the results. Some believed that the prognosis was poor compared with patients with a known primary because proper management of the extracranial tumor was delayed 5.…”
mentioning
confidence: 98%